2004
DOI: 10.1037/0012-1649.40.6.1148
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Performance on the Iowa Gambling Task: Implications for the Development of Decision Making and Ventromedial Prefrontal Cortex.

Abstract: Healthy adolescents (79 girls, 66 boys), ages 9-17, completed the Iowa Gambling Task (IGT; A. Bechara, A. R. Damasio, H. Damasio, & S. W. Anderson, 1994) as well as working memory (digit span) and behavioral inhibition (go/no-go) tasks. Cross-sectional age-related changes were seen on all 3 tasks. Gender differences were seen in IGT deck preference and attentional variables (i.e., go/no-go hit rate and forward digit span). After age, gender, and general intellectual abilities were controlled for, IGT performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

42
304
3
19

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 361 publications
(380 citation statements)
references
References 60 publications
42
304
3
19
Order By: Relevance
“…Improved executive function in adolescence is reflected in better performance with age on tasks known to activate the dorsolateral prefrontal cortex, such as relatively difficult tests of spatial working memory (Conklin et al, 2007) or especially challenging tests of response inhibition (Luna et al, 2001); and the ventromedial prefrontal cortex, such as the Iowa Gambling Task (Crone & van der Molen, 2004;Hooper, Luciana, Conklin, & Yarger, 2004). Although some tests of executive function simultaneously activate both the dorsolateral and ventromedial regions, there is some evidence that the maturation of these regions may take place along somewhat different timetables, with performance on exclusively ventromedial tasks reaching adult levels somewhat earlier than performance on exclusively dorsolateral tasks (Conklin et al, 2007;Hooper et al, 2004).…”
Section: Structural Maturation Of the Cognitive Control Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Improved executive function in adolescence is reflected in better performance with age on tasks known to activate the dorsolateral prefrontal cortex, such as relatively difficult tests of spatial working memory (Conklin et al, 2007) or especially challenging tests of response inhibition (Luna et al, 2001); and the ventromedial prefrontal cortex, such as the Iowa Gambling Task (Crone & van der Molen, 2004;Hooper, Luciana, Conklin, & Yarger, 2004). Although some tests of executive function simultaneously activate both the dorsolateral and ventromedial regions, there is some evidence that the maturation of these regions may take place along somewhat different timetables, with performance on exclusively ventromedial tasks reaching adult levels somewhat earlier than performance on exclusively dorsolateral tasks (Conklin et al, 2007;Hooper et al, 2004).…”
Section: Structural Maturation Of the Cognitive Control Systemmentioning
confidence: 99%
“…Improved executive function in adolescence is reflected in better performance with age on tasks known to activate the dorsolateral prefrontal cortex, such as relatively difficult tests of spatial working memory (Conklin et al, 2007) or especially challenging tests of response inhibition (Luna et al, 2001); and the ventromedial prefrontal cortex, such as the Iowa Gambling Task (Crone & van der Molen, 2004;Hooper, Luciana, Conklin, & Yarger, 2004). Although some tests of executive function simultaneously activate both the dorsolateral and ventromedial regions, there is some evidence that the maturation of these regions may take place along somewhat different timetables, with performance on exclusively ventromedial tasks reaching adult levels somewhat earlier than performance on exclusively dorsolateral tasks (Conklin et al, 2007;Hooper et al, 2004). In one recent study of age differences in cognitive performance using tasks known to differentially activate these two prefrontal regions, there was age-related improvement into middle adolescence on both types of tasks, but there were no significant correlations between performance on the ventromedial and dorsolateral tasks, suggesting that maturation of the ventromedial prefrontal cortex may be a developmentally distinct process from the maturation of the dorsolateral prefrontal cortex (Hooper et al, 2004).…”
Section: Structural Maturation Of the Cognitive Control Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the psychological literature has shown that adults perform better than adolescents on the IGT, who, in turn, perform better than children as demonstrated by (i) the positive relationship between age and IGT performance (Crone & van der Molen, 2004;Crone et al, 2005;Hooper et al, 2004), and (ii) ascribed poor decision-making to an non-linear development of subcortical and prefrontal regions that underpin decisionmaking (Smith et al, 2012). This decision-making impairment, exemplified by the perseverance of bad choices when performing the IGT, has been detected in several studies utilizing psychopathological populations, such as drug-and alcohol-addicted (Bechara et al, 2001;Goudriaan et al, 2005Goudriaan et al, , 2006Lorains et al, 2014;Monterosso et al, 2001;Wiehler & Peters, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In one study (Hooper et al, 2004), three different age cohorts were compared (9-10 years, 11-13 years, 14-17 years).…”
Section: Introductionmentioning
confidence: 99%